Potassium‐catalyzed steam gasification of ash‐free lignite coal with CO2 capture. (18th August 2017) - Rasi, Negar Manafi; Mostafavi, Ehsan; Retuta, Maria Angelica; Rahman, Moshfiqur M.; Gupta, Raj; Mahinpey, Nader
Abstract: The purpose of this research was to study steam gasification of ash‐free coal integrated with CO2 capture in the presence of a K2 O catalyst for enhancement of the key water‐gas shift reaction and promotion of hydrogen production. To achieve this goal, gasification experiments on ash‐free coal (AFC) were carried out at varying temperatures (600, 650, 675, 700, and 750 °C) with a sorbent‐to‐carbon (CaO/C) ratio of 2 and a catalyst (K2 O) loading of 0.2 g/g (20 weight percent (wt%)) in a fixed‐bed reactor equipped with a gas chromatography analyzer. The sorbent‐to‐carbon (CaO/C) ratio of 2 is based on dry and ash‐free basis. The CaO/C ratio and K2 O wt% were chosen to maximize hydrogen production based on our previously determined optimal values. The AFC was originally extracted from raw lignite coal using organic solvents, which allowed the sorption‐enhanced gasification to be conducted with minimal ash‐catalyst interactions. The effect of temperature on the yield and the initial reaction rate were investigated. The optimal reaction temperature of 675 °C was determined. Carbon balance and final carbon conversions were calculated based on the residue analysis. Activation energy was also calculated using intrinsic kinetics of the reaction. In this study, using AFC offered the potential advantage of operating the gasification process with catalyst recycle.